Mobile anthropometry in Division I baseball athletes: evaluation of an existing application and the development of new equations - Haynes, H.; Tinsley, G. M.; Swafford, S. H.; Compton, A. T.; Moore, J.; Donahue, P. T.; Graybeal, A. J. (The Journal of Strength and Conditioning Research, 2024)
The purpose of this study was to evaluate the agreement between mobile application and dual-energy x-ray absorptiometry (DXA)-derived body composition parameters in a group of Division I (DI) collegiate baseball athletes and to develop new equations for this population using this mobile technique. A total of 41 (age: 20.5 ± 1.5 years; DXA %fat: 18.9 ± 4.6%) DI collegiate baseball athletes underwent body composition assessments using DXA and a mobile anthropometric application. Total and appendicular body composition estimates were produced from this mobile application using previously developed equations and evaluated against the reference (DXA) in the complete sample of athletes. Least absolute shrinkage and selection operator regressions were then used to develop new equations using the mobile application in a portion of the athletes (n = 34) and subsequently tested in the remaining athletes (n = 7). In the complete sample, no body composition estimate using the mobile application's existing equations (R2: 0.00-0.68) demonstrated equivalence with DXA, including estimates of %fat (R2: 0.37; root-mean-squared error [RMSE]: 3.74%), fat mass (FM), and total (appendicular lean mass [ALM]) and leg lean mass ([ALMlegs] R2: 0.67-0.68; RMSE: 3.43-4.86 kg). In the testing sample, estimates produced from the newly developed equations demonstrated acceptable performance when compared to DXA, most notably %fat (R2: 0.80; RMSE: 3.66%), FM, ALM, and ALMlegs (R2: 0.55-0.87; RMSE: 0.74-3.46 kg). Previously developed equations using mobile anthropometrics may not demonstrate acceptable agreement with DXA in DI collegiate baseball athletes, and newly developed equations specific to this group may be more suitable. Those employing these newly developed equations should use caution until further external cross-validation is performed.